Allocating resources for land protection using continuous optimization: biodiversity conservation in the United States. Issue 6 (5th May 2020) - Armsworth, Paul R.; Benefield, Amy E.; Dilkina, Bistra; Fovargue, Rachel; Jackson, Heather B.; Le Bouille, Diane; Nolte, Christoph
Abstract: Spatial optimization approaches that were originally developed to help conservation organizations determine protection decisions over small spatial scales are now used to inform global or continental scale priority setting. However, the different decision contexts involved in large‐scale resource allocation need to be considered. We present a continuous optimization approach in which a decision‐maker allocates funding to regional offices. Local decision‐makers then use these funds to implement habitat protection efforts with varying effectiveness when evaluated in terms of the funder's goals. We illustrate this continuous formulation by examining the relative priority that should be given to different counties in the coterminous United States when acquiring land to establish new protected areas. If weighting all species equally, counties in the southwest United States, where large areas can be bought cheaply, are priorities for protection. If focusing only on species of conservation concern, priorities shift to locations rich in such species, particularly near expanding exurban areas facing high rates of future habitat conversion (e.g., south‐central Texas). Priorities for protection are sensitive to what is assumed about local ecological and decision‐making processes. For example, decision‐makers who doubt the efficacy of local land protection efforts should focus on a few key areas, while optimistic decision‐makers should disperse funding more widely. Efforts to inform large‐scale conservation priorities should reflect better the types of choice that decision‐makers actually face when working over these scales. They also need to report the sensitivity of recommended priorities to what are often unstated assumptions about local processes affecting conservation outcomes.